PROPAGANDA ELEITORAL NA DEMOCRACIA MIDIÁTICA: A VITÓRIA DA EMOÇÃO NA ELEIÇÃO PRESIDENCIAL DE 2014 NO BRASIL - CATARIN, Roberto Bianchi (2016)
This research has the purpose of political communication focusing on canvass, in the context of media democracy. On this basis, outlines to the research problem: studying how the canvass has appropriated from the media democracy context to expose your messages, the use of reason and emotion, selling dreams to the voter and other issues such as criticism of the opponent and the promises they do. The research objective is to highlight the types of prepared content to be transmitted to voters who attend the free election time, analyze the arguments, the quality and content of such placements, as well as highlight the distinctions between them, and evaluating their effectiveness, their main features, which set them apart and what resources they used to attract attention and the popular vote. The methodology was the analysis of content, since you want to understand what are the main signs and characteristics defined by the parties and the candidates at the time disclosed. Six categories have been defined for the analysis of ten videos of television free Airtime the three candidates, both the first as the second round. We conclude that the candidate Dilma Rousseff was the most advantage of all strategic artifices of political communication, electoral propaganda, appropriate of media democracy, with strong emotional appeal in the categories analyzed, resulting in a narrow victory, the most disputed today however, a positive result for the reelection campaign of President.